PHENOMENON OF RURAL COMMUNITY BEHAVIOR IN ONLINE PAYMENT TRANSACTIONS POST COVID-19 IN LAMONGAN REGENCY, EAST JAVA - Lilik Nurcholidah; Moh. Muklis Sulaeman; Henny Mahmudah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
Online shopping transactions are carried out with a number of supporting facilities that must be available. Among them are the existence of communication technology devices, internet network access, inter-regional cargo courier services and the development of adequate infrastructure. So that with adequate supporting facilities, online payment transactions can be made to reach almost all regions in the world and even reach consumers in rural communities. Rural Community or what is often referred to as rural community is a society that is always associated with modesty, backwardness, traditionalism and isolation. In this case, modesty is often associated with simplicity in the behavior of rural communities such as in the delivery of words and in meeting simple needs. Meanwhile, underdevelopment is a condition of delay in the development or progress of something that supports the sustainability of rural life. The next is traditionalism which is a teaching by emphasizing the traditions received from previous generations as a way of life. The research method in this study is a qualitative method with a phenomenological approach. a social phenomenon that occurs in the behavior of online payment transactions in rural communities in villages in Lamongan Regency. In accordance with the phenomenon of ERG Theory, online shopping transactions have become a shopping style trend in rural communities in Lamongan Regency since before the COVID-19 pandemic. Then the Covid 19 pandemic has not become an obstacle for rural communities to make online payment transactions. It was found that the behavior of rural consumers in online shopping transactions went through several stages of purchasing decisions. However, transactions are often carried out impulsively. Rural communities in Lamong Regency are still enthusiastic and want to make transactions even though they cannot feel the benefits and advantages of online shopping to the fullest.